2020
DOI: 10.29037/ajstd.600
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Signatures in the Context of Landscape Evolution: Evidence from Citanduy Watershed, Java, Indonesia

Abstract: The impact of humans on landscapes may differ across regions because anthropogenic intervention on the respective landscapes occurs in different human-induced contexts. This study was designed to assess the human-induced landscape evolution of the Citanduy Watershed, Java, Indonesia, and determine its anthropogenic signatures. Several approaches were used, namely anthropogenic landscape identification, anthropogenic soil development, sediment analysis, and monitoring of changes to Segara Anakan lagoon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Among the coasts in Class 3, Palatar Agung and Pasir Putih have lower physical parameters than human parameters, and even Palatar Agung has poor water colour and clarity with cloudy brown water. Palatar Agung's poor colour and clarity are due to its location at the Citanduy watershed outlet, which has long experienced high erosion (Malawani et al, 2020). On the other hand, Pasir Putih, Karapyak, and Muaragatah have excellent water clarity in the reef areas that form tidal pools.…”
Section: Classmentioning
confidence: 99%
“…Among the coasts in Class 3, Palatar Agung and Pasir Putih have lower physical parameters than human parameters, and even Palatar Agung has poor water colour and clarity with cloudy brown water. Palatar Agung's poor colour and clarity are due to its location at the Citanduy watershed outlet, which has long experienced high erosion (Malawani et al, 2020). On the other hand, Pasir Putih, Karapyak, and Muaragatah have excellent water clarity in the reef areas that form tidal pools.…”
Section: Classmentioning
confidence: 99%
“…Moreover, environmental experts have suggested that the world has shifted to the Anthropocene, where humans have a global influence on the environment [10]. Evidence of the onset of the Anthropocene suggests that future watershed management requires prioritizing and addressing various anthropogenic phenomena [11]. Humans as geomorphological agents have influenced many processes in the watershed, such as accelerating erosion and sedimentation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Human activities is strongly influence to morphological change and natural processes modification in the different intensity of geomorphic processes. Anthropogenic processes also commonly generated the recent landscape evolution [3]. The existence of various anthropogenic landforms in a certain location can be the basis for studying the potential natural disasters [4].…”
Section: Introductionmentioning
confidence: 99%